STRATEGIC MANAGEMENT OF HOTEL COMPANIES: CASE STUDY OF HOTEL COMPANIES IN VOJVODINA (SERBIA) - VUKOSAV, Svetlana; ĆURČIĆ, Nevena; VUK, Garača; ČEROVIĆ, Slobodan; CURAKOVIĆ, Danka (Revista de turism - studii și cercetări în turism, 2014)
Contemporary approaches to the management of the company are focused on achieving long-term success of the company in its complex and changing environment. Company as part of the wider environment, must adapt to the changing environment in order to survive, growing and developing. The task of strategic management is to enable the enterprise in the tourism industry to rationally and promptly react to changes in the environment in which it carries out its business and general activity. The aim of this paper is to determine whether and to what extent the process of the strategic management is being implemented in hotels in Vojvodina(that are changed ownership structure) and what is their response to the competitive pressures and opportunities, and demands and needs of consumers Strategic positioning in order to achieve sustainable competitive advantage through product differentiation and segmentation of demand is imperative for success of hotel companies in Vojvodina.